Performance of Ultrasonic Membrane Anaerobic System (UMAS) in Membrane Fouling Control - Nour, A. H.; Azhari, H. Nour (IJESIT, 2013)
The primary objective of this study was to evaluate the effects of the organic loading rate (OLR) on the performance of an ultrasonic-assisted membrane anaerobic system (UAMAS) treating Palm Oil Mill Effluent (POME), based on the following indicators: (i) methane gas contents, (ii) chemical oxygen demand (COD) removal efficiency, and (iii) effluent variability (phenol, suspended solids, volatile fatty acids, and pH stability).Six steady states were attained as a part of a kinetic study that considered concentration ranges of 15,830 to 21,600 mg/l for mixed liquor suspended solids (MLSS) and 9,450 to 18,200 mg/l for mixed liquor volatile suspended solids (MLVSS). Kinetic equations from Monod, Contois and Chen & Hashimoto were employed to describe the kinetics of POME treatment at organic loading rates ranging from 0.5 to 15 kg COD/m3/d. The removal efficiency of COD was from 93 to 98.7 % with a hydraulic retention time (HRT) of 4 days. The growth yield coefficient, Y, was found to be 0.59 g VSS/g COD, the specific microorganism decay rate was 0.26 d-1, and the methane gas yield production rate was between 0.264 l/g COD/d and 0.47 l/g COD/d.